Receiving material for Micro LED (Light Emitting Diode) laser mass transfer as well as preparation method and application of receiving material
By designing a bearing material containing hydrogen-containing silicone oil and vinyl-containing silicone oil, combined with nanofillers and other components, the problem of insufficient performance in the huge transfer of Micro LED chips is solved, and an efficient and accurate transfer process is achieved, which improves the transfer yield and lighting bond yield of the chip.
Patent Information
- Application Number
- CN202510041653.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-12-31
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve the huge transfer of high efficiency, accuracy and high yield of Micro LED chips, especially during the transfer process, which requires good performance such as initial viscosity, energy storage value, energy storage modulus, support force and tensile strength.
By designing a bearing material containing hydrogen-containing silicone oil and vinyl-containing silicone oil, combined with nanofillers, catalysts, inhibitors, compatibilizers and tackifiers, a bearing material with excellent performance is prepared, and a huge transfer of Micro LED chips is achieved.
It improves the transfer efficiency and yield of Micro LED chips, realizes an efficient and high-precision transfer process, and improves the lighting yield and bonding yield of RGB chips.
Smart Images

Figure CN119875576A_ABST
Abstract
Description
[0001] This application claims priority to patent application number 202411994034.7 (the filing date of the prior application is December 31, 2024, and the name of the invention is a receiving material for Micro LED laser mass transfer, and its preparation method and application. Technical Field
[0002] The present invention belongs to the technical field of Micro LED mass transfer, and specifically relates to a receiving material for Micro LED laser mass transfer, and a preparation method and application thereof. Background Art
[0003] Micro LED technology, with its advantages of high brightness, high contrast, low power consumption, fast response time and long life, shows great application potential in the field of consumer electronics, especially in applications such as virtual reality (VR), augmented reality (AR), smart watches and large displays. One of the core challenges is mass transfer technology. Since the size of Micro LED is much smaller than that of traditional LED, it will be extremely difficult to accurately and efficiently transfer a large number of Micro LED chips from the growth substrate to the target substrate or driver circuit board. Mass transfer technology requires not only extremely high precision to ensure that each Micro LED chip can be accurately placed in the predetermined position, but also high yield and efficiency to achieve cost-effectiveness and mass production.
[0004] The selection of mass transfer materials is crucial to achieving an efficient and low-cost Micro LED manufacturing process. It needs to have good initial adhesion, appropriate storage value, storage modulus, support force, and sufficient tensile strength and TTV to support the stable transfer of Micro LED chips during the transfer process, while also ensuring long-term reliability and performance after the transfer. In addition, the mass transfer material should also have good compatibility with the Micro LED chip and the target substrate, as well as controllability during the transfer process to achieve an efficient manufacturing process.
[0005] How to provide a Micro LED chip receiving material that can receive and transfer the chip to the substrate after laser release has become a technical problem that needs to be solved urgently. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a receiving material for Micro LED laser mass transfer and its preparation method and application. The present invention designs the specific composition of the receiving material to prepare a controllable and efficient receiving material, realizes the mass transfer of Micro LED chips, and improves the efficiency and yield of the transfer of Micro LED chips.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a receiving material for Micro LED laser mass transfer, wherein the receiving material comprises the following components in parts by weight:
[0009]
[0010] The silicone oil includes hydrogen-containing silicone oil and vinyl-containing silicone oil.
[0011] The present invention designs the specific composition of the receiving material and prepares a receiving material with excellent properties such as good initial adhesion, appropriate energy storage value, storage modulus, supporting force, sufficient tensile strength, TTV, etc. through the coordination of specific amounts of components, thereby realizing the mass transfer of Micro LED chips and improving the efficiency and yield of the transfer of Micro LED chips.
[0012] The receiving material provided by the present invention can effectively receive the chips after release and sorting, and perform laser welding process with high yield. The process operation is simple, and the production efficiency can be effectively improved. Under the efficient and high-precision transfer process, the lighting yield and bonding yield of the RGB chip can be simultaneously improved. It has strong practicality and high accuracy. When used for Micro LED laser mass transfer, the thickness of the receiving film can be adjusted according to needs, the viscosity can also be adjusted, and there are multiple curing methods. The main characteristics include good TTV, i.e., uniformity of the film surface reception, and a large equipment process window.
[0013] In the present invention, silicone oil is the main component of the receiving material, the main component of the glue, and the main component of the curing and cross-linking reaction. It constitutes the skeleton of the silicone molecular chain segment and has good acid and alkali resistance. It can play a good role in receiving, bonding, supporting and toughening. It is also the main material for better receiving micro light-emitting diode chips; silicone resin is the auxiliary resin of the material system, which is a minor component of the glue, has a high molecular weight, and can play a good role in adjusting temperature resistance, substrate adhesion and toughening performance; nanofiller is an auxiliary material of the material system. The formula without reinforcing auxiliary materials usually has a low cohesive density and weak intermolecular interaction, so the comprehensive performance such as mechanical strength is poor. Nanofillers mainly play the role of adjusting rheological properties, improving mechanical properties, enhancing thermal stability, promoting vulcanization reaction, and enhancing dispersibility; the catalyst is an initiator that catalyzes the curing and crosslinking reaction. Different types of catalysts have different initiation conditions, such as light, heat, moisture, ultraviolet light, etc. The use of different catalysts (preferably (trimethyl) methylcyclopentadiene platinum, rhodium acetylacetonate, platinum acetylacetonate, etc.) can adjust the hardness, toughness, elongation at break, energy storage value, etc. of the final cured product; the inhibitor is an auxiliary agent that inhibits curing and crosslinking, and maintains the stability of the catalyst during storage and transportation. Due to the instability of the formula, a natural crosslinking reaction is easily catalyzed by the catalyst, so the inhibitor is An indispensable additive in the formula. Adding inhibitors can greatly improve the stability of the overall system of the formula and make it more in line with the needs of industrial production. In addition, inhibitors can also control the curing reaction rate and inhibit undesirable side reactions. Compatibilizers are used to enhance the compatibility of polymers with poor compatibility, reduce interfacial tension, increase dispersion, and improve phase stability. They can improve the compatibility between different components in the reaction system and avoid uneven spin coating film surface caused by stratification or glue phase separation. They play an important role in improving the TTV of the final cured product and ensuring the flatness of the film surface. Tackifiers are additives used to adjust the adhesion between the substrate and the colloid, and between the chip and the colloid, and to improve the adhesion performance of the material.
[0014] The present invention prepares a receiving material with excellent performance by selecting a combination of hydrogen-containing silicone oil and vinyl-containing silicone oil. The receiving material has excellent surface initial adhesion, hardness, energy storage value and elongation at break.
[0015] At the same time, the present invention can improve the hardness, tensile strength and toughness of the receiving material, increase the viscosity of the receiving material, improve the thixotropy, help improve its processing performance, and adjust the applicable film thickness by controlling the amount of the nanofiller within a specific range. If the amount of the nanofiller is too small, the comprehensive performance of the prepared receiving material is poor; if the amount of the nanofiller is too large, it is not conducive to the dispersion of the nanofiller in the receiving material, and agglomeration will be formed, thereby affecting the subsequent forming process of the receiving material to prepare the receiving film.
[0016] In the present invention, the weight proportion of silicone oil in the receiving material can be 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts or 90 parts.
[0017] The weight proportion of the silicone resin in the receiving material may be 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts or 10 parts, etc.
[0018] The weight proportion of the nanofiller in the receiving material can be 0.1 parts, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, etc.
[0019] The weight proportion of the catalyst in the receiving material can be 0.03 parts, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts, etc.
[0020] The weight proportion of the inhibitor in the receiving material can be 0.03 parts, 0.05 parts, 0.1 parts, 0.15 parts, 0.2 parts, 0.25 parts, 0.3 parts, 0.35 parts, 0.4 parts, 0.45 parts or 0.5 parts, etc.
[0021] The weight proportion of the compatibilizer in the receiving material can be 0.1 parts, 0.2 parts, 0.5 parts, 0.7 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, etc.
[0022] The weight proportion of the tackifier in the receiving material can be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, etc.
[0023] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.
[0024] As a preferred technical solution of the present invention, the mass ratio of the hydrogen-containing silicone oil to the vinyl-containing silicone oil is 1:(10-15), for example, it can be 1:10, 1:10.5, 1:11, 1:11.5, 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5 or 1:15, etc.
[0025] The present invention further controls the mass ratio of hydrogen-containing silicone oil and vinyl-containing silicone oil within a specific range, which can further improve the comprehensive performance of the receiving material. If the mass ratio of hydrogen-containing silicone oil and vinyl-containing silicone oil is too small, that is, the amount of hydrogen-containing silicone oil is too little, then when the receiving material is subsequently used to receive the chip, the receiving material is insufficiently solidified, thereby affecting the mechanical properties of the final receiving material. When it is in a liquid-like state, its support for the chip is insufficient and it cannot enter the next process; if the mass ratio of hydrogen-containing silicone oil and vinyl-containing silicone oil is too large, that is, the amount of hydrogen-containing silicone oil is too much, then when the receiving material is subsequently used to receive the chip, the solidified receiving material is too hard, which will cause the final receiving chip to break.
[0026] Preferably, the hydrogen-containing silicone oil is selected from any one of methyl hydrogen-containing silicone oil, methylethoxy hydrogen-containing silicone oil, fluorine-containing hydrogen-containing silicone oil, carboxyl-modified hydrogen-containing silicone oil, mercapto-modified hydrogen-containing silicone oil, epoxy-modified hydrogen-containing silicone oil, ammonia-modified hydrogen-containing silicone oil, acrylic acid-modified hydrogen-containing silicone oil or polyether-modified hydrogen-containing silicone oil, or a combination of at least two thereof, and is further preferably methyl hydrogen-containing silicone oil and / or polyether-modified hydrogen-containing silicone oil.
[0027] Preferably, the fluorine-containing and hydrogen-containing silicone oil includes methyltrifluoropropyl silicone oil.
[0028] Preferably, the vinyl-containing silicone oil is selected from any one of methyl vinyl silicone oil, methyl phenyl vinyl silicone oil, methyl chlorophenyl vinyl silicone oil, phenyl vinyl silicone oil or hydroxy silicone oil, or a combination of at least two thereof.
[0029] Preferably, the weight proportion of silicone oil in the receiving material is 75-85 parts, for example, it can be 75 parts, 76 parts, 77 parts, 78 parts, 79 parts, 80 parts, 81 parts, 82 parts, 83 parts, 84 parts or 85 parts.
[0030] As a preferred technical solution of the present invention, the rotational viscosity of the silicone resin is 500-20000 mPa·s (for example, it can be 500 mPa·s, 600 mPa·s, 800 mPa·s, 1000 mPa·s, 2000 mPa·s, 3000 mPa·s, 5000 mPa·s, 7000 mPa·s, 10000 mPa·s, 12000 mPa·s, 14000 mPa·s, 16000 mPa·s, 18000 mPa·s or 20000 mPa·s, etc.), preferably 500-10000 mPa·s.
[0031] Preferably, the silicone resin is selected from any one or a combination of at least two of phenolic resin-modified silicone resin, polyester resin-modified silicone resin, epoxy resin-modified silicone resin, polyurethane-modified silicone resin or unmodified silicone resin.
[0032] Preferably, the weight proportion of the silicone resin in the receiving material is 5-8 parts, for example, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts or 8 parts.
[0033] Preferably, the nanofiller is selected from any one of white carbon black, fumed silica, graphene, carbon nanotubes, multi-walled carbon nanotubes, montmorillonite, and nano calcium carbonate, or a combination of at least two thereof.
[0034] Preferably, the weight proportion of the nanofiller in the receiving material is 0.5-3 parts, for example, 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts.
[0035] As a preferred technical solution of the present invention, the catalyst is selected from any one or a combination of at least two of a platinum catalyst, a palladium catalyst, a rhodium catalyst, a nickel catalyst, an ionic liquid complex metal catalyst or a heterogeneous catalyst.
[0036] Preferably, the catalyst is selected from any one or a combination of at least two of chloroplatinic acid, triphenylphosphine palladium (Ph3P), bis(1,3-divinyl-1,1,3,3-tetramethyldisiloxane)platinum, platinum((0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, (trimethyl)methylcyclopentadieneplatinum, rhodium acetylacetonate or platinum acetylacetonate, and is further preferably any one or a combination of at least two of (trimethyl)methylcyclopentadieneplatinum, rhodium acetylacetonate or platinum acetylacetonate.
[0037] Preferably, the weight proportion of the catalyst in the receiving material is 0.05-0.1 parts, for example, it can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or 1 parts.
[0038] Preferably, the inhibitor is selected from any one or a combination of at least two of alkoxysilane acetylenic compounds, nitrogen-containing organic compound inhibitors, phosphorus-containing organic compound inhibitors, sulfur-containing organic compound inhibitors, heavy metal ion compound inhibitors, acetylenic compound inhibitors, and acetylenic alcohol inhibitors.
[0039] Preferably, the inhibitor is selected from any one of butynedioic acid esters, 1-ethynylcyclohexanol, 3-phenyl-1-butyn-3-ol, 3,5-propyl-1-octyne-3-ol, methylbutynol, 4-methyl-1-butyn-3-ol, ethynylcyclohexanol, P2-1 or P2-2, or a combination of at least two thereof.
[0040] Preferably, the weight proportion of the inhibitor in the receiving material is 0.05-0.1 parts, for example, it can be 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts or 1 parts.
[0041] As a preferred technical solution of the present invention, the compatibilizer includes any one of a silicon-acrylic compatibilizer, an epoxy or a polydimethylsiloxane, or a combination of at least two thereof.
[0042] Preferably, the weight proportion of the compatibilizer in the receiving material is 0.1-3 parts (for example, 0.1 parts, 0.2 parts, 0.5 parts, 0.7 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts, etc.), and more preferably 0.1-1 parts.
[0043] Preferably, the tackifier is selected from any one or a combination of at least two of an acrylate-containing silicone tackifier (PHMS-g-HDDA), an ester-containing silicone tackifier (PHMS-g—HDDA), an alkoxy-containing silane compound, a silicon hydrogen-containing silane compound, a siloxane oligomer or an ester-containing silicone tackifier.
[0044] Preferably, the tackifier is selected from any one of octamethylcyclotetrasiloxane, dodecamethylcyclohexasiloxane diallyl maleate or diallyl maleate, or a combination of at least two thereof.
[0045] Preferably, the weight proportion of the tackifier in the receiving material is 3-8 parts, for example, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts or 8 parts.
[0046] In a second aspect, the present invention provides a method for preparing a receiving material for Micro LED laser mass transfer as described in the first aspect, the preparation method comprising the following steps:
[0047] Prepare glue A: mix the vinyl-containing organosilicon oil, organosilicon resin and catalyst to obtain glue A;
[0048] Prepare B glue: mix hydrogen-containing organic silicone oil, nano filler, inhibitor, compatibilizer and tackifier to obtain B glue;
[0049] Mix glue A and glue B to obtain the receiving material for Micro LED laser mass transfer.
[0050] It should be noted that, in the present invention, when preparing glue B, in order to obtain glue B with good stability and convenient preparation process, it is necessary to add the inhibitor, compatibilizer and tackifier into the hydrogen-containing organosilicon oil in sequence and mix them.
[0051] As a preferred technical solution of the present invention, the method for mixing in the preparation of gelatin A includes: using a high-speed disperser for high-speed stirring.
[0052] Preferably, the rotation speed of the high-speed stirring is 1000-2000rpm (for example, it can be 1000rpm, 1100rpm, 1200rpm, 1300rpm, 1400rpm, 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm or 2000rpm, etc., and more preferably 1300rpm), and the time is ≥4h (for example, it can be 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h or 8h, etc.).
[0053] Preferably, the temperature of the high-speed stirring is ≤35°C, for example, it may be 20°C, 22°C, 24°C, 25°C, 27°C, 28°C, 30°C, 32°C, 33°C or 35°C.
[0054] Preferably, the method for mixing in the preparation of glue B comprises: using a planetary stirring kettle for mixing and stirring.
[0055] Preferably, the mixing and stirring speed is 300-500rpm (for example, it can be 300rpm, 320rpm, 340rpm, 360rpm, 380rpm, 400rpm, 420rpm, 440rpm, 460rpm, 480rpm or 500rpm, etc., and more preferably 300rpm), and the time is ≥12h (for example, it can be 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h or 16h, etc.).
[0056] As a preferred technical solution of the present invention, the method for mixing glue A and glue B includes stirring, the stirring speed is 300-800rpm (for example, it can be 300rpm, 350rpm, 400rpm, 450rpm, 500rpm, 550rpm, 600rpm, 650rpm, 700rpm, 750rpm or 800rpm, etc., and more preferably 430rpm), the time is ≥12h, and the temperature is ≤35℃ (for example, it can be 20℃, 22℃, 24℃, 25℃, 27℃, 28℃, 30℃, 32℃, 33℃ or 35℃, etc.).
[0057] Preferably, the mixing of the A glue and the B glue further includes a post-processing method, and the post-processing method includes filtration.
[0058] In the present invention, there is no special restriction on the size of the filter element used for filtration, and the filter elements commonly used in the art are applicable, including but not limited to: using filter elements with sizes of 1 μm, 0.45 μm, and 0.22 μm in sequence for filtration.
[0059] As a preferred technical solution of the present invention, the method for preparing the receiving material for Micro LED laser mass transfer specifically includes the following steps:
[0060] Preparation of glue A: placing vinyl-containing silicone oil in a high-speed disperser, adding silicone resin and catalyst thereto, stirring and mixing at high speed at 1000-2000 rpm and temperature ≤35°C for ≥4h to obtain glue A;
[0061] Preparation of B glue: placing hydrogen-containing organosilicon oil in a planetary stirring kettle, adding an inhibitor, a compatibilizer and a tackifier thereto, mixing and stirring at 300-500 rpm for ≥12 h to obtain B glue;
[0062] Add glue A to glue B, stir and mix for ≥12 hours at a rotation speed of 300-800 rpm and a temperature of ≤35°C, and then filter to obtain the receiving material for Micro LED laser mass transfer.
[0063] In a third aspect, the present invention provides an application of a receiving material for Micro LED laser mass transfer as described in the first aspect, wherein the receiving material is used for Micro LED laser mass transfer;
[0064] Preferably, the process method of using the receiving material for Micro LED laser mass transfer comprises the following steps:
[0065] Coating the receiving material of the Micro LED laser mass transfer onto the second substrate and curing it to obtain a second substrate provided with a temporary receiving layer;
[0066] Placing a first substrate provided with a laser induced release layer and a second substrate provided with a temporary receiving layer in a mass transfer device, so that the LED chip and the temporary receiving layer are arranged opposite to each other and are not connected; the LED chip is arranged on a side of the laser induced release layer away from the first substrate;
[0067] The laser irradiates the laser induced release layer to release the LED chip at the corresponding position to the temporary receiving layer of the second substrate, thereby completing the Micro LED laser mass transfer;
[0068] Preferably, the thickness of the receiving material coated with the Micro LED laser mass transfer is 5-150μm, for example, it can be 50μm, 10μm, 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm or 150μm, etc.
[0069] In the present invention, the coating method includes spin coating, and the spin coating rotation speed is 300-2000rpm (for example, it can be 300rpm, 400rpm, 600rpm, 800rpm, 1000rpm, 1200rpm, 1400rpm, 1600rpm, 1800rpm or 2000rpm, etc.), and the time is 20-120s (for example, it can be 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s, 110s or 120s, etc.).
[0070] Preferably, the curing temperature is ≥160°C (for example, it may be 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C, 210°C or 220°C, etc.), preferably 160-200°C.
[0071] Preferably, the curing time is 5-20 min, for example, it can be 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min or 20 min, etc.
[0072] Preferably, the distance between the surface of the laser induced release layer away from the first substrate and the surface of the temporary receiving layer away from the second substrate is 20-200μm, for example, it can be 20μm, 40μm, 60μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm or 200μm.
[0073] Preferably, the energy density of the laser irradiation is 50-300 mJ / cm 2 , for example, it can be 50mJ / cm 2 、70mJ / cm 2 、100mJ / cm 2 、120mJ / cm 2 、150mJ / cm 2 、180mJ / cm 2 、200mJ / cm 2 、230mJ / cm 2 、250mJ / cm2 、270mJ / cm 2 or 300mJ / cm 2 wait.
[0074] It should be noted that the present invention has no special restrictions on the specific selection of the first substrate and the second substrate, and any commonly used substrates in the art are applicable, including but not limited to sapphire substrates.
[0075] Meanwhile, the present invention does not have any special restrictions on the material of the laser induced release layer, and any commonly used substrates in the art are applicable, including but not limited to LAP811 (purchased from Shenzhen Huaxun Semiconductor Materials Co., Ltd.).
[0076] Compared with the prior art, the present invention has the following beneficial effects:
[0077] (1) The present invention designs the specific composition of the receiving material and prepares a receiving material with excellent properties such as good initial adhesion, appropriate energy storage value, storage modulus, supporting force, sufficient tensile strength, TTV, etc. through the coordination of specific amounts of each component, thereby realizing the mass transfer of Micro LED chips and improving the efficiency and yield of the transfer of Micro LED chips.
[0078] (2) The present invention can further improve the comprehensive performance of the receiving material by controlling the mass ratio of hydrogen-containing silicone oil to vinyl-containing silicone oil within a specific range.
[0079] (3) The receiving material provided by the present invention can effectively receive the chips after release and sorting, and perform laser welding process with high yield. The process operation is simple, which can effectively improve production efficiency. Under the efficient and high-precision transfer process, the lighting yield and bonding yield of the RGB chip can be simultaneously improved. It has strong practicality and high accuracy. When used for Micro LED laser mass transfer, the thickness of the receiving film can be adjusted according to needs, the viscosity can also be adjusted, and there are multiple curing methods. The main characteristics are good TTV, that is, the uniformity of the film surface, and a large equipment process window. BRIEF DESCRIPTION OF THE DRAWINGS
[0080] Figure 1 This is a schematic diagram of chip accuracy after Micro LED laser mass transfer using the receiving material provided in Example 1. DETAILED DESCRIPTION
[0081] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0082] The sources of some components in the following examples and comparative examples are as described in Table 1:
[0083] Table 1
[0084] Components illustrate Hydrogen silicone oil Guangdong Zhongke Hongtai New Materials Co., Ltd. Vinyl silicone oil Shanghai Guiyou New Material Technology Co., Ltd. Pure silicone resin Guangzhou Delta Silicone Technology Development Co., Ltd. Epoxy resin modified silicone resin Shandong Dayi Chemical Co., Ltd. White Carbon Black Shanghai Kaiyin Chemical Co., Ltd. Graphene Shanghai Liwusheng New Materials Technology Development Co., Ltd. Rhodium acetylacetonate MacLean's reagent (Trimethyl)methylcyclopentadienylplatinum MacLean's reagent Chloroplatinic acid Kunming Borui Metal Materials Co., Ltd. Butynedioate Olilon (Jining) Chemical Co., Ltd. Ethynyl cyclohexanol MacLean's reagent Dimethicone Guangzhou Shenghong Chemical Co., Ltd. Octamethylcyclotetrasiloxane MacLean's reagent Diallyl Maleate MacLean's reagent
[0085] Example 1-Example 11, Comparative Example 1-Comparative Example 8
[0086] Example 1-Example 11 and Comparative Example 1-Comparative Example 8 respectively provide a receiving material for Micro LED laser mass transfer, and the raw materials for preparing the receiving material are shown in Table 2-Table 3 below, and the amount of each component in Table 2-Table 3 is in parts by weight.
[0087] The preparation method of the above-mentioned receiving material for Micro LED laser mass transfer is as follows:
[0088] Preparation of glue A: placing vinyl-containing silicone oil in a high-speed disperser, adding silicone resin and catalyst thereto, stirring at a high speed of 1500 rpm and a temperature of 25° C., mixing for 6 hours, and obtaining glue A;
[0089] Preparation of B glue: placing hydrogen-containing organosilicon oil in a planetary stirring kettle, adding an inhibitor, a compatibilizer and a tackifier thereto in sequence, mixing and stirring at 300 rpm for 15 hours to obtain B glue;
[0090] Glue A was added to glue B, and the mixture was stirred for 15 hours at a rotation speed of 430 rpm and a temperature of 30°C. Then, the mixture was filtered using filter elements with sizes of 1 μm, 0.45 μm, and 0.22 μm, respectively, to obtain the receiving material for Micro LED laser mass transfer.
[0091] Table 2
[0092]
[0093] Table 3
[0094]
[0095]
[0096] Micro LED laser mass transfer is performed using the receiving materials provided in the above embodiments and comparative examples. The specific process method is as follows:
[0097] (1) A laser induced release layer material (LAP811, purchased from Shenzhen Huaxun Semiconductor Materials Co., Ltd.) was coated on a sapphire substrate with a coating thickness of 20 μm;
[0098] (2) placing a sapphire substrate coated with a laser induced release layer material at 100° C. to evaporate the solvent to form a film, thereby obtaining a sapphire substrate 1 provided with a laser induced release layer;
[0099] (3) placing the sapphire substrate 2 provided with the LED chip and the sapphire substrate 1 provided with the laser induced release layer opposite to each other and performing thermal compression bonding at 60° C. for 10 minutes;
[0100] (4) using laser lift-off technology to process the sapphire substrate 2 provided with the LED chip, and transferring the LED chip to the side of the laser induced release layer away from the sapphire substrate 1;
[0101] (5) removing and cleaning the sapphire substrate 2 to obtain a sapphire substrate 1 provided with a laser induced release layer, wherein an LED chip is provided on a side of the laser induced release layer away from the sapphire substrate 1;
[0102] (6) Spin coating the receiving material of the Micro LED laser mass transfer onto the sapphire substrate 3, with a spin coating speed of 800 rpm, a time of 60 s, and a thickness of 50 μm;
[0103] (7) Curing the sapphire substrate 3 with the receiving material of Micro LED laser mass transfer spin-coated at 180° C. for 12 min to obtain a sapphire substrate 3 with a temporary receiving layer;
[0104] (8) placing the sapphire substrate 1 provided with a laser induced release layer obtained in step (5) (the side of the laser induced release layer away from the first substrate is provided with an LED chip) and the sapphire substrate 3 provided with a temporary receiving layer obtained in step (6) in a mass transfer device, so that the LED chip and the temporary receiving layer are arranged opposite to each other and are not connected;
[0105] The distance between the surface of the laser induced release layer away from the first substrate and the surface of the temporary receiving layer away from the second substrate is 110 μm;
[0106] The energy density used is 150mJ / cm 2 The multi-band laser irradiates the laser-induced release layer to release the LED chips at the corresponding positions to the temporary receiving layer of the sapphire substrate 3, thus completing the Micro LED laser mass transfer;
[0107] (9) Use a 1064nm laser to transfer the LED chip on the surface of the temporary receiving layer to the TFT substrate for laser mass welding.
[0108] The performance of the receiving materials provided in the above embodiments and comparative examples, and the yield of the chips when using the receiving materials provided in the above embodiments and comparative examples for Micro LED laser mass transfer were characterized, and the specific tests were as follows:
[0109] The following categories are the characterization of the chip when performing Micro LED laser mass transfer for the receiving material:
[0110] 1. Initial adhesion: The instrument sensor automatically obtains the initial adhesion after the universal testing machine indenter contacts the rubber material;
[0111] 2. Hardness: GB / T 531.1-2008;
[0112] 3. Energy storage value: The company develops its own testing method: nanoindentation mechanical testing system, which obtains data curve by pressing down with a constant force, and data can be read from the obtained curve.
[0113] 4. Storage modulus: The company develops its own testing method: the rotational rheometer is used for storage modulus testing, and the shear modulus is used for characterization. The storage modulus value can be directly read from the obtained data curve.
[0114] 5. Rebound depth: Use a micrometer to measure the indentation depth, and the reading can be read directly on the display.
[0115] 6. Support force: The company developed its own testing method: After the universal testing machine is pressed down, the rubber surface is observed. The force corresponding to no collapse is the support force.
[0116] 7.Tensile strength: GB / T 528-2009
[0117] 8.TTV: The step meter tests 5 points on the membrane surface and then calculates the maximum and minimum values
[0118] The following categories are the characterization of the chip when performing Micro LED laser mass transfer for the receiving material:
[0119] 1. Chip transfer yield: Take samples for observation under an optical microscope, transfer yield = X2 / X1*100%;
[0120] Among them, X1 is the number of Micro LED chips on the growth substrate, and X2 is the number of Micro LED chips successfully transferred to the receiving layer (successful transfer means that the Micro LED chips have not flipped or broken).
[0121] After using the receiving material provided in Example 1 to perform Micro LED laser mass transfer, the chip accuracy diagram is as follows: Figure 1 As shown by Figure 1 It can be seen that the transfer accuracy in the figure is close to 100%, and it can be seen that no transfer has occurred in the RGB chips in the figure.
[0122] The above performance test results are detailed in Table 4 below:
[0123] Table 4
[0124]
[0125]
[0126] “ / ” indicates that the data has not been tested.
[0127] From the above content, it can be seen that the present invention designs the specific composition of the receiving material and prepares a receiving material with good initial adhesion, appropriate energy storage value, storage modulus, supporting force, sufficient tensile strength, TTV and other excellent properties through the coordination of specific amounts of each component, thereby realizing the mass transfer of Micro LED chips and improving the efficiency and yield of the transfer of Micro LED chips. The initial adhesion is 0.05-2.8N, the hardness is 4-35, the energy storage value is 163,000-682,000, the storage modulus is 13.0-17.0MPa, the rebound depth is 0.43-0.78μm, the supporting force is 75-200N, the tensile strength is 2.0-9.0MPa, and the chip transfer yield is >99.99%.
[0128] The present invention further improves the comprehensive performance of the receiving material by controlling the mass ratio of hydrogen-containing silicone oil and vinyl-containing silicone oil within a specific range. The initial adhesion is 0.05-2.6N, the hardness is 12-35, the energy storage value is 258,000-631,000, the storage modulus is 13.0-17.0MPa, the rebound depth is 0.43-0.66μm, the supporting force is 100-180N, the tensile strength is 2.3-8.0MPa, TTV is less than 3%, and the chip transfer yield is greater than 99.99%.
[0129] It can be seen from Example 1 and Example 5 that the present invention can further improve the comprehensive performance of the receiving material by selecting silicone oil with hydrogen in the side chain.
[0130] It can be seen from Example 1, Examples 10-11 and Comparative Examples 1-2 that the present invention prepares a receiving material with excellent performance by controlling the amount of nanofiller within a specific range.
[0131] It can be seen from Examples 1 to 11 and Comparative Examples 3 to 8 that the present invention designs the specific composition of the receiving material to prepare a receiving material with excellent performance.
[0132] In summary, the present invention designs the specific composition of the receiving material and prepares a receiving material with excellent properties such as good initial adhesion, appropriate energy storage value, storage modulus, supporting force, sufficient tensile strength, TTV, etc. through the coordination of specific amounts of each component, thereby realizing the mass transfer of Micro LED chips and improving the efficiency and yield of the transfer of Micro LED chips. The receiving material can effectively receive the chips after release and sorting, and perform laser welding process with high yield. The process operation is simple, and the production efficiency can be effectively improved. Under the efficient and high-precision transfer process, the lighting yield of the RGB chip and the bonding yield are simultaneously improved, and the practicability is strong and the accuracy is high.
[0133] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A receiving material for Micro LED laser mass transfer, characterized in that: The receiving material includes the following components in parts by weight: The silicone oil includes hydrogen-containing silicone oil and vinyl-containing silicone oil.
2. The receiving material for Micro LED laser mass transfer according to claim 1, characterized in that: The mass ratio of the hydrogen-containing silicone oil to the vinyl-containing silicone oil is 1:(10-15); Preferably, the hydrogen-containing silicone oil is selected from any one of methyl hydrogen-containing silicone oil, methylethoxy hydrogen-containing silicone oil, fluorine-containing hydrogen-containing silicone oil, carboxyl-modified hydrogen-containing silicone oil, mercapto-modified hydrogen-containing silicone oil, epoxy-modified hydrogen-containing silicone oil, ammonia-modified hydrogen-containing silicone oil, acrylic acid-modified hydrogen-containing silicone oil or polyether-modified hydrogen-containing silicone oil, or a combination of at least two thereof, and is further preferably methyl hydrogen-containing silicone oil and / or polyether-modified hydrogen-containing silicone oil; Preferably, the vinyl-containing silicone oil is selected from any one of methyl vinyl silicone oil, methyl phenyl vinyl silicone oil, methyl chlorophenyl vinyl silicone oil, phenyl vinyl silicone oil or hydroxy silicone oil, or a combination of at least two thereof; Preferably, the weight proportion of silicone oil in the receiving material is 75-85 parts.
3. The receiving material for Micro LED laser mass transfer according to claim 1 or 2, characterized in that: The rotational viscosity of the silicone resin is 500-20000 mPa·s, preferably 500-10000 mPa·s; Preferably, the silicone resin is selected from any one or a combination of at least two of a phenolic resin-modified silicone resin, a polyester resin-modified silicone resin, an epoxy resin-modified silicone resin, a polyurethane-modified silicone resin or an unmodified silicone resin; Preferably, the weight proportion of the silicone resin in the receiving material is 5-8 parts; Preferably, the nanofiller is selected from any one or a combination of at least two of white carbon black, fumed silica, graphene, carbon nanotubes, multi-walled carbon nanotubes, montmorillonite, and nano calcium carbonate; Preferably, the weight proportion of the nanofiller in the receiving material is 0.5-3 parts.
4. The receiving material for Micro LED laser mass transfer according to any one of claims 1 to 3, characterized in that: The catalyst is selected from any one or a combination of at least two of a platinum catalyst, a palladium catalyst, a rhodium catalyst, a nickel catalyst, an ionic liquid complex metal catalyst or a heterogeneous catalyst; Preferably, the catalyst is selected from any one or a combination of at least two of chloroplatinic acid, triphenylphosphine palladium (Ph3P), bis(1,3-divinyl-1,1,3,3-tetramethyldisiloxane) platinum, platinum ((0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, platinum (0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane, (trimethyl) methylcyclopentadiene platinum, rhodium acetylacetonate or platinum acetylacetonate, and is further preferably any one or a combination of at least two of (trimethyl) methylcyclopentadiene platinum, rhodium acetylacetonate or platinum acetylacetonate; Preferably, the weight percentage of the catalyst in the receiving material is 0.05-0.1 parts; Preferably, the inhibitor is selected from any one or a combination of at least two of alkoxysilane acetylenic compounds, nitrogen-containing organic compound inhibitors, phosphorus-containing organic compound inhibitors, sulfur-containing organic compound inhibitors, heavy metal ion compound inhibitors, acetylenic compound inhibitors, and acetylenic alcohol inhibitors; Preferably, the inhibitor is selected from any one or a combination of at least two of butynedioic acid esters, 1-ethynylcyclohexanol, 3-phenyl-1-butyn-3-ol, 3,5-propyl-1-octyne-3-ol, methylbutynol, 4-methyl-1-butyn-3-ol, ethynylcyclohexanol, P2-1 or P2-2; Preferably, the weight proportion of the inhibitor in the receiving material is 0.05-0.1 parts.
5. The receiving material for Micro LED laser mass transfer according to any one of claims 1 to 4, characterized in that: The compatibilizer includes any one or a combination of at least two of a silicon-acrylic compatibilizer, an epoxy or a polydimethylsiloxane; Preferably, the weight proportion of the compatibilizer in the receiving material is 0.1-3 parts, more preferably 0.1-1 parts; Preferably, the tackifier is selected from any one or a combination of at least two of an acrylate-based organosilicon tackifier, an ester-based organosilicon tackifier, an alkoxy-containing silane compound, a silane compound containing a silicon hydrogen group, a siloxane oligomer or an ester-based organosilicon tackifier; Preferably, the tackifier is selected from any one or a combination of at least two of octamethylcyclotetrasiloxane, dodecamethylcyclohexasiloxane diallyl maleate or diallyl maleate; Preferably, the weight proportion of the tackifier in the receiving material is 3-8 parts.
6. A method for preparing a receiving material for Micro LED laser mass transfer according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Prepare glue A: mix the vinyl-containing organosilicon oil, organosilicon resin and catalyst to obtain glue A; Prepare B glue: mix hydrogen-containing organic silicone oil, nano filler, inhibitor, compatibilizer and tackifier to obtain B glue; Mix glue A and glue B to obtain the receiving material for Micro LED laser mass transfer.
7. The preparation method according to claim 6, characterized in that: The method for mixing in the preparation of glue A includes: using a high-speed disperser for high-speed stirring; Preferably, the speed of the high-speed stirring is 1000-2000 rpm, and the time is ≥4h; Preferably, the high-speed stirring temperature is ≤35°C; Preferably, the method for mixing in the preparation of glue B comprises: using a planetary stirring kettle for mixing and stirring; Preferably, the mixing and stirring is carried out at a speed of 300-500 rpm (preferably 300 rpm) for a time of ≥12 h.
8. The preparation method according to claim 6 or 7, characterized in that: The method for mixing the A glue and the B glue comprises stirring, wherein the stirring speed is 300-800 rpm, the time is ≥12h, and the temperature is ≤35°C; Preferably, the mixing of the A glue and the B glue further includes a post-processing method, and the post-processing method includes filtration.
9. An application of a receiving material for Micro LED laser mass transfer as claimed in any one of claims 1 to 5, characterized in that: The receiving material is used for Micro LED laser mass transfer.
10. The use according to claim 9, characterized in that: The process method of using the receiving material for Micro LED laser mass transfer includes the following steps: Coating the receiving material of the Micro LED laser mass transfer onto the second substrate and curing it to obtain a second substrate provided with a temporary receiving layer; Placing a first substrate provided with a laser induced release layer and a second substrate provided with a temporary receiving layer in a mass transfer device, so that the LED chip and the temporary receiving layer are arranged opposite to each other and are not connected; the LED chip is arranged on a side of the laser induced release layer away from the first substrate; The laser irradiates the laser induced release layer to release the LED chip at the corresponding position to the temporary receiving layer of the second substrate, thereby completing the Micro LED laser mass transfer; Preferably, the thickness of the receiving material coated with the Micro LED laser mass transfer is 5-150 μm; Preferably, the curing temperature is ≥160°C, preferably 160-200°C; Preferably, the curing time is 5-20 min; Preferably, the distance between the surface of the laser induced release layer away from the first substrate and the surface of the temporary receiving layer away from the second substrate is 20-200 μm; Preferably, the energy density of the laser irradiation is 50-300 mJ / cm 2 .